2015
DOI: 10.1136/bmj.h5231
|View full text |Cite
|
Sign up to set email alerts
|

Taking time out of training to shed light on “the dark side”

Abstract: describe their Darzi fellowship, a year long secondment opportunity in leadership and management for healthcare professionals The importance of effective management and leadership is increasingly accepted in medicine, moving from "the dark side to centre stage."[1] However, few trainees are exposed to formal leadership opportunities. On many courses theory predominates over hands-on experience and reflective practice, and trainees are often observers rather than active participants in management decisions. Som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…For example, Seidle, Fernandez, and Perry (2016) highlight how leaders can benefit from "a combination of coaching, classroom instruction, feedback, and experiential training. " Conn et al (2016) identified the empowering nature of leadership training for participants to effect change, develop networks, and build thinking that is "reflexive, critical, and strategic." This comment also leads to consideration for future FWB studies, where adoption of an action learning approach that captures longer term perceptions and changes in behavior (as suggested above) is worthwhile.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Seidle, Fernandez, and Perry (2016) highlight how leaders can benefit from "a combination of coaching, classroom instruction, feedback, and experiential training. " Conn et al (2016) identified the empowering nature of leadership training for participants to effect change, develop networks, and build thinking that is "reflexive, critical, and strategic." This comment also leads to consideration for future FWB studies, where adoption of an action learning approach that captures longer term perceptions and changes in behavior (as suggested above) is worthwhile.…”
Section: Discussionmentioning
confidence: 99%
“…The programme is strategically important since the NHS in England requires more “change agent” clinicians armed with healthcare improvement and redesign of care skills (Wachter, 2016; Darzi, 2008). Overall in the NHS “trainees are often observers rather than active participants in management decisions” (Conn et al , 2015), and the Fellowship importantly actively promotes a collaborative learning approach to leadership and management. A review of relevant literature on leadership and clinician leadership development (LD) follows.…”
Section: Introductionmentioning
confidence: 99%
“…Organisations include NHS England, NICE, royal colleges, and BMJ. The scheme has close links to similar schemes in Wales, Northern Ireland, and Scotland 17…”
Section: Job Insecurity and The Futurementioning
confidence: 97%